Triglyceride-glucose index is associated with lupus nephritis and gender disparity in systemic lupus erythematosus patients - Lin, Shuhan; Tao, Liangying; Yang, Fan; Shu, Ruilu; Cheng, Weimeng; Wen, Lihui; Zhang, Huayong (Frontiers in Medicine, 2025)
ObjectiveRecent studies investigated that triglyceride glucose (TyG) index and triglyceride (TG) are associated with an elevated likelihood of developing and worsening chronic kidney disease (CKD). We aimed to evaluate the correlation between the TyG index and TG with lupus nephritis (LN), respectively, and explore its value in monitoring LN.Methods1,192 Systemic Lupus Erythematosus (SLE) patients were involved in this cross-sectional investigation. The presence or absence of LN was used to divide the individuals involved into two distinct categories. Multivariate logistic regression, restricted cubic spline, and subgroup analyses were applied to explore the connection between the TyG index and TG with LN, respectively.ResultsAccording to the study, the TyG index and TG were dose-dependently positively correlated with LN. After accounting for additional factors, each standard deviation of an upsurge in the TyG index and TG corresponded to a higher risk for LN by 36.4 and 34%, respectively. Besides, the adjusted ORs (with 95% CIs) for LN were precisely 1.625 (1.097, 2.405) and 1.756 (1.193, 2.585) when comparing the highest tertile to the lowest tertile of the TyG index and TG, respectively. Additionally, both TyG index and TG were significantly positively correlated with LN in age and body mass index (BMI) subgroups, and these two indicators were independently associated with LN in female SLE patients but not in male SLE patients, respectively.ConclusionBoth the elevated TyG index and TG were linked to LN on their own and gender disparity in SLE patients, which suggests that the TyG index and TG could be beneficial in the early screening for those with LN.